Sikap Agent Of Change Guru Dan Pegawai Di SMKN 4 Padang - Muhammad, Muhammad Berkah; Muhammad Irsyad (CV. ITTC INDONESIA, 2025)
This study aims to examine the role of teachers as agents of change in improving the quality of education at SMK Negeri 4 Padang. Teachers are viewed not only as transmitters of knowledge but also as key drivers in fostering the transformation of students' values, attitudes, and skills. In the context of 21st-century educational dynamics and the challenges of the Industrial Revolution 4.0, teachers are required to possess competence, innovation, and responsiveness to change. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and questionnaires. The findings indicate that teachers and staff at SMK Negeri 4 Padang play a strategic role as agents of change, although there are still obstacles such as limited facilities, low access to technology, and individual readiness to embrace innovation. The success of educational transformation is influenced by collaboration, leadership support, as well as teachers’ mental preparedness and professionalism. This study contributes to a better understanding of the strategies and readiness that teachers need in order to effectively meet the demands of educational change.